2020
DOI: 10.1002/ece3.6311
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary tracking is determined by differential selection on demographic rates and density dependence

Abstract: Recent ecological forecasts predict that ~25% of species worldwide will go extinct by 2050. However, these estimates are primarily based on environmental changes alone and fail to incorporate important biological mechanisms such as genetic adaptation via evolution. Thus, environmental change can affect population dynamics in ways that classical frameworks can neither describe nor predict. Furthermore, often due to a lack of data, forecasting models commonly describe changes in population demography by summariz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 69 publications
0
10
2
Order By: Relevance
“…Other factors such as adaptation to environmental changes and population regulation by density-dependence are also worthy of study given their impact on the risk of extinction (Vinton and Vasseur 2020). For instance, Brook et al (2006) found smaller MVPs under three (negative) density-dependence models than under two density-independent models, the MVPs for the latter being around two orders of magnitude larger than those for the former.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as adaptation to environmental changes and population regulation by density-dependence are also worthy of study given their impact on the risk of extinction (Vinton and Vasseur 2020). For instance, Brook et al (2006) found smaller MVPs under three (negative) density-dependence models than under two density-independent models, the MVPs for the latter being around two orders of magnitude larger than those for the former.…”
Section: Discussionmentioning
confidence: 99%
“…Impact of environmental variation and temporal autocorrelation on underlying genetics Moderate environmental variation can optimise selection, and ultimately evolutionary tracking [45,46] (but see [2]). In contrast, the ability of populations to evolutionarily track a shifting adaptive peak can increase with greater temporal autocorrelation [25].…”
Section: Mechanisms Of Evolutionary Response To Changing Environments...mentioning
confidence: 99%
“…It is usually assumed that a more variable environment is detrimental for populations. However, recent syntheses show that the effect of environmental variability can have both positive and negative effects on population growth rates [2,59]. For example, disparities in population size responses to environmental variability are influenced by differences in the magnitude of density dependence [60].…”
Section: Mechanisms Of Ecological Response To Changing Environments: ...mentioning
confidence: 99%
See 2 more Smart Citations